Pengaruh Model Problem Based Learning Berbantu Talkshow Terhadap Komunikasi Lisan Siswa Pada Materi Perubahan Lingkungan - Resa Vilonia Nursela; Umi Fatmawati; Kistantia Elok Mumpuni (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by the talkshow method on students’ oral communication skills in environmental change topics. The research was conducted at SMAN 2 Surakarta using a quantitative approach with a quasi-experimental design cluster random sampling involving two classes: the experimental group received the PBL model with talkshow, and the control group used conventional PBL. Data were collected using an observation sheet covering seven indicators of oral communication: introduction,thesis statement, subject knowledge, movement, eye contact, fluency, and voice. The results showed that students in the experimental group had higher average scores in oral communication skills than those in the control group. Statistical analysis using the Kolmogorov-Smirnov normality test, Levene’s test of homogeneity, and t-test. The t-test result of 0.003 showed a significant differences between the two groups. The implementation of the PBL model assisted by talkshow enhanced students' confidence, engagement, and verbal communication during biology learning. This finding implies that integrating interactive talkshow methods into PBL can effectively improve students’ oral communication skills in high school settings.